Wittgenstein and the life we live with language - Hertzberg, Lars (Anthem studies in Wittgenstein, 2022)
"This work is guided by the idea that Wittgenstein's thought opens the door to a more profound break with the philosophical tradition than has been generally recognized. It brings this insight to bear on some basic problems of philosophy"--